The cancer growth suppressor gene mda-7 selectively induces apoptosis in human breast cancer cells and inhibits tumor growth in nude mice - Su, Zao-zhong (The National Academy of Sciences, 1998)
A differentiation induction subtraction hybridization strategy is being used to identify and clone genes involved in growth control and terminal differentiation in human cancer cells. This scheme identified melanoma differentiation associated gene-7 (mda-7), whose expression is up-regulated as a consequence of terminal differentiation in human melanoma cells. Forced expression of mda-7 is growth inhibitory toward diverse human tumor cells. The present studies elucidate the mechanism by which mda-7 selectively suppresses the growth of human breast cancer cells and the consequence of ectopic expression of mda-7 on human breast tumor formation in vivo in nude mice. Infection of wild-type, mutant, and null p53 human breast cancer cells with a recombinant type 5 adenovirus expressing mda-7, Ad.mda-7 S, inhibited growth and induced programmed cell death (apoptosis). Induction of apoptosis correlated with an increase in BAX protein, an established inducer of programmed cell death, and an increase in the ratio of BAX to BCL-2, an established inhibitor of apoptosis. Infection of breast carcinoma cells with Ad.mda-7 S before injection into nude mice inhibited tumor development. In contrast, ectopic expression of mda-7 did not significantly alter cell cycle kinetics, growth rate, or survival in normal human mammary epithelial cells. These data suggest that mda-7 induces its selective anticancer properties in human breast carcinoma cells by promoting apoptosis that occurs independent of p53 status. On the basis of its selective anticancer inhibitory activity and its direct antitumor effects, mda-7 may represent a new class of cancer suppressor genes that could prove useful for the targeted therapy of human cancer.